A new active peptide from Neptunea arthritica cumingii exerts protective effects against gentamicin-induced sensory-hair cell injury in zebrafish. (2nd January 2022) - Zhang, Shanshan; Gao, Yan; He, Qiuxia; Zhang, Yun; Han, Liwen; Jin, Meng; Liu, Tong; Liu, Kechun; Sun, Chen
Abstract: Gentamicin is commonly used for effective treatment of severe Gram-negative bacterial infections. However, its use is being increasingly restricted owing to the ototoxic effects attributed to it. Gentamicin-induced ototoxicity is thought to be related with apoptosis induced by reactive oxygen species (ROS). In this study, we found a novel active peptide from Neptunea arthritica cumingii with otoprotective effects and no significant embryotoxic effects. The combined application of gentamicin and this novel active peptide helped sensory-hair cells to protect themselves from lethal ROS accumulation. This, in turn, reduced the expression of three genes ( caspase-3, caspase-9, Bax ), and thereby, the sensory-hair cell apoptosis promoted by ROS accumulation upon gentamicin administration. Our findings provided new insights into the prevention of gentamicin-induced hearing loss.